Don't wanna lose you - Richie, Lionel; Polygram Records (New York : PolyGram Records, 1996)
Contains two versions of the single.
Radio edit (4:37) -- Album version (4:57).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Popular music